The Arbuthnot anthology of children's literature - Arbuthnot, May Hill, 1884-1969 (Scott, Foresman, 1971)
A collection of poetry, folklore, fantasy, short stories, biographies, and other non-fiction. Includes a history and discussion of children's literature and suggestions for using this literature with children.